2020
DOI: 10.1177/1559325820936161
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Based Drug Delivery System: A Patient-Friendly Chemotherapy for Oncology

Abstract: Chemotherapy is widely used to treat cancer. The toxic effect of conventional chemotherapeutic drugs on healthy cells leads to serious toxic and side effects of conventional chemotherapy. The application of nanotechnology in tumor chemotherapy can increase the specificity of anticancer agents, increase the killing effect of tumors, and reduce toxic and side effects. Currently, a variety of formulations based on nanoparticles (NPs) for delivering chemotherapeutic drugs have been put into clinical use, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(81 citation statements)
references
References 126 publications
1
80
0
Order By: Relevance
“…The trial performed by Kaklamani et al showed a pCR of 17.9%, a result similar to a previously reported clinical trial that used lapatinib in combination with weekly paclitaxel in women with inflammatory breast cancer, however, it showed a decrease in grade 3 diarrhea [20,35]. The use of abraxane has also been reported to improve overall response and survival, as well as to decrease hypersensitivity reactions, reducing the use of corticosteroids in advance [36]. The trial performed by Yardley et al reported a lower overall response rate in comparison to similar studies.…”
Section: Discussionsupporting
confidence: 73%
“…The trial performed by Kaklamani et al showed a pCR of 17.9%, a result similar to a previously reported clinical trial that used lapatinib in combination with weekly paclitaxel in women with inflammatory breast cancer, however, it showed a decrease in grade 3 diarrhea [20,35]. The use of abraxane has also been reported to improve overall response and survival, as well as to decrease hypersensitivity reactions, reducing the use of corticosteroids in advance [36]. The trial performed by Yardley et al reported a lower overall response rate in comparison to similar studies.…”
Section: Discussionsupporting
confidence: 73%
“…This allows for an understanding of why the concerted inhibition of NHE1 plus CA inhibitors improves the efficacy of paclitaxel by mediating its induction of apoptosis in triple-negative BC cells and its metastases [ 44 , 46 , 52 , 139 , 167 , 179 , 202 , 239 , 241 , 247 , 248 ]. More recently, liposomal preparations and nanodrugs of DOXO and others compounds have been trying to find a place in the treatment of BC and other tumors, and clinical trials with these methodologies are underway [ 249 ].…”
Section: Other Ph-related Available Therapies In Breast Cancer Trementioning
confidence: 99%
“…This allows understanding why the concerted inhibition of NHE1 plus CA inhibitors improves the efficacy of Paclitaxel by mediating in its induction of apoptosis in triple-negative BC cells and its metastases [36,38,44,128,156,168,192,230,232,238,239]. More recently, liposomal preparations and nanodrugs of DOXO and others compounds are trying to find a place in the treatment of BC and other tumors, and clinical trials with these methodologies are under way [240].…”
Section: Doxorubicin (Doxo) and Paclitaxelmentioning
confidence: 99%